Network Externalities, Dominant Value Margins, and Equilibrium Uniqueness - Jay Pil Choi; Christodoulos Stefanadis (Center for Economic Studies and ifo Institute (CESifo), 2022)
We examine tippy network markets that accommodate price discrimination. The analysis shows that when a mild equilibrium refinement, the monotonicity criterion, is adopted, network competition may have a unique subgame-perfect equilibrium regarding the winner's identity; the prevailing brand may be fully determined by its product features. We bring out the concept of the dominant value margin, which is a metric of the effectiveness of divide-and-conquer strategies. The supplier with the larger dominant value margin may always sell to all customers in equilibrium. Such a market outcome is not always socially efficient since a socially inferior supplier may prevail if has a stand-alone-benefit advantage and only a modest network-benefit disadvantage.
Keywords: L13; L40; D43; 330; network externalities; equilibrium uniqueness; price discrimination; monotonicity criterion; dominant value margin; divide and conquer